2023
DOI: 10.3389/fmicb.2023.1260071
|View full text |Cite
|
Sign up to set email alerts
|

Fruit waste: a current perspective for the sustainable production of pharmacological, nutraceutical, and bioactive resources

Shankar Prasad Sha,
Debabrata Modak,
Sourav Sarkar
et al.

Abstract: Fruits are crucial components of a balanced diet and a good source of natural antioxidants, that have proven efficacy in various chronic illnesses. Various kinds of waste generated from fruit industries are considered a global concern. By utilizing this fruit waste, the international goal of “zero waste” can be achieved by sustainable utilization of these waste materials as a rich source of secondary metabolites. Moreover, to overcome this waste burden, research have focused on recovering the bioactive compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 205 publications
(289 reference statements)
0
2
0
Order By: Relevance
“…Antioxidants prevent adverse alterations of lipids, proteins and DNA. Therefore, the application of exogenous antioxidants can help in dealing with oxidative stress [81][82][83][84].…”
Section: Bioactive Compounds In Fruit Wastementioning
confidence: 99%
“…Antioxidants prevent adverse alterations of lipids, proteins and DNA. Therefore, the application of exogenous antioxidants can help in dealing with oxidative stress [81][82][83][84].…”
Section: Bioactive Compounds In Fruit Wastementioning
confidence: 99%
“…Many fruits and vegetables contain these antioxidant phenolics, which contribute to their health benefits [11]. Despite the antioxidant benefits of fruit consumption, studies have shown that the non-edible wastes of many fruits are notable sources of phenolics, which is influential in their reported medicinal properties [12][13][14]. For instance, the seed of avocado fruit has ethnomedicinal applications in mental disorders and obesity [15], while the peel has cosmetic applications [16].…”
Section: Introductionmentioning
confidence: 99%